Electronic Structure Insights into the Solvation of Magnesium Ions with Cyclic and Acyclic Carbonates. Issue 17 (23rd October 2015) - Shakourian‐Fard, Mehdi; Kamath, Ganesh; Sankaranarayanan, Subramanian K. R. S.
Abstract: A computational framework to rank the solvation behavior of Mg 2+ in carbonates by using molecular dynamics simulations and density functional theory is reported. Based on the binding energies and enthalpies of solvation calculated at the M06‐2X/6‐311++G(d, p) level of theory and the free energies of solvation from ABF‐MD simulations, we find that ethylene carbonate (EC) and the ethylene carbonate:propylene carbonate (EC:PC) binary mixture are the best carbonate solvents for interacting with Mg 2+ . Natural bond orbital and quantum theory of atoms in molecules analyses support the thermochemistry calculations with the highest values of charge transfer, perturbative stabilization energies, electron densities, and Wiberg bond indices being observed in the Mg 2+ (EC) and Mg 2+ (EC:PC) complexes. The plots of the noncovalent interactions indicate that those responsible for the formation of Mg 2+ carbonate complexes are strong‐to‐weak attractive interactions, depending on the regions that are interacting. Finally, density of state calculations indicate that the interactions between Mg 2+ and the carbonate solvents affects the HOMO and LUMO states of all carbonate solvents and moves them to more negative energy values. Abstract : All solved : The solvation behavior of carbonates with magnesium ions, as predicted by molecular dynamics and density functional theory, show that a larger free energy of solvation and binding of such complexes is associated with larger charge transfer and that such interactions are electrostatic in nature.